Ruthless valley [large type] - Dundee, Wayne D. (Dundee, Wayne D. Lone McGantry western, 2025)
"Lone McGantry is no stranger to danger. But when a favor for a friend embroils him in treachery, he finds himself at a crossroads. After a man's belief in his runaway wife's innocence drives him to chase her into the heart of danger, Lone is called upon to aid in the search, risking everything to save him from the clutches of those with malicious intent. Standing in their path is attorney Niles Lavin and his ruthless investigator, both determined to seize control of a valley rich with untapped resources. As loyalties are tested, Lone realizes that fulfilling his obligation may demand more than he ever imagined and force him to confront the true depths of his resolve in a battle full of ruthless enemies."--